Efektivitas Penertiban Pedagang Kreatif Lapangan Oleh Satuan Polisi Pamong Praja Di Jalan Jawa Kota Palangka Raya - Fatchurahman Fatchurahman; Sofiah Sofiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This research aims to examine and analyze the effectiveness of creative traders in the field by the police unit of Pamong Praja at Jalan Jawa City Palangka Raya. This research uses qualitative research methods. The source of the data is derived from the Police unit organization of the city Palangka Raya, PKL, the community in the large market of the street Java City Palangka Raya Raya, as well as documents that support this research. Data collection techniques by observation, interviews, documentation. Data analysis techniques include data reduction, data display and conclusion drawing Verification. Based on the results of this study, it is known that the use of Creative Trader Field (PKL) is done because of the number of creative traders who have been made use of public places in the trading activities so that the implementation by Satpol PP. As well as the effectiveness of regulating and supporting factors and the implementation of creative traders field by Satpol PP on Jalan Java City Palangka Raya is insufficient infrastructure to perform regulation such as transportation tools that is too old to carry out patrol activities and the lack of budget earned funds.